Eksplorasi Ekstrak Wortel (Daucus Carota L.) Sebagai Tabir Surya pada Analisis SPF (Sun Protection Factor) Sediaan Lotion - Muhammad Elfani Tasya; Agung Nur Cahyanta; Desi Sri Rejeki (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Sunlight is the main source of energy for life, but ultraviolet radiation can have negative impacts on the skin, such as sunburn, pigmentation, wrinkles, premature aging, and the risk of skin damage due to excessive exposure. One way to protect the skin from these effects is to use sunscreen. Carrots contain antioxidant compounds that can bind free radicals and prevent cell damage due to oxidation, so they have the potential to be used as a natural ingredient in making sunscreen. This research aims to formulate and test the physical properties of carrot extract lotion as a sunscreen and determine the extract concentration that has the optimal Sun Protection Factor (SPF) value. The method used is experimental by making lotion formulations, testing their physical properties, and measuring the SPF value of each formulation. The research results showed that the KN, F1, F2, and F3 lotion formulations had a semi-solid form which met the formulation requirements. However, KN's SPF value is only 1.23 which does not meet sunscreen standards. Meanwhile, F1 has SPF 8.3 (extra effect category), F2 with SPF 15.06 and F3 with SPF 24.1 (ultra category). F3 shows the best results because with SPF 24.1, this formulation is close to SPF 25 which can protect the skin for up to 4 hours with twice daily use. The higher the concentration of carrot extract, the better its effectiveness in lotion formulation as a sunscreen.